Control Of Epilachna Vigintioctopuntata Fab. (Coleoptera: Coccinellidae) Using Some Indigenous Plant Extracts - Islam, Kamrul; Islam, M Saiful; Ferdousi, Zennat (Journal of Life and Earth Science, 2012)
Epilachna vigintioctopunctata is an important pest that causes considerable economic losses to many crops including egg-plants. The crude aqueous extracts of leaves from three indigenous plants namely Ricinus communis, Calotropis procera and Datura metel were used against this beetle aiming at its control under laboratory conditions. Larvicidal bioassays of the extracts showed the following order of toxicity: R. communis (LC50=18.40%) > C. procera (LC50=23.70%) > D. metel (LC50=29.61%). Subsequent data on some vital life-history traits were promising because the extracts significantly reduced both oviposition and egg-hatch, prolonged larval duration (P<0.001), and inhibited pupae formation and adult emergence (P<0.05). However, female ratio was not significantly affected by the treatments. Relevance of these findings on the control of this phytophagous species has been discussed. DOI: http://dx.doi.org/10.3329/jles.v6i0.9725 JLES 2011 6: 75-80